142 Leaking nasopharyngeal aspirate (NPA) during transit: the impact of a safety alert and importance of proper laboratory specimen transportation. (December 2018) - Musabaike, W; Wu, Y; Morris, C; Rockenbach, T; Heales, S
Abstract : Background: Nasopharyngeal aspirates (NPA) are commonly collected for prompt diagnosis of viral respiratory infections which is crucial for positive patient outcomes and implementation of infection control measures. At the Great Ormond Street Hospital for Children, NPA samples were either hand-delivered to the laboratory or transported via the chute. In 2016, there was a high number of leaking NPA in the chute system due to the use of containers unapproved for the chute. This not only caused safety issues but also delays in the transportation of other laboratory samples as the entire chute system had to be shut down for decontamination. On 24 March 2017, a safety alert was issued which stated that all NPA samples must be delivered by hand only. This study examined the impact of the safety alert, which was part of the Quality Improvement project tackling laboratory pre-analytical errors. Methods: Data for NPA samples received between 01/03/2016 – 30/04/2018 were extracted from the Laboratory Information System. The number of leaking NPA samples and the sample transport time before and after the release of the safety alert were compared. Results: There was a 65% drop in the number of leaking NPA samples after the issue of the safety alert. The transport time has increased with higher impact observed on the samples collected in the late evening. Conclusion: The safety alert was effective in reducing the number of leaking NPA samples received in the laboratory but has increased the sample transport time. Until a new sample container that is approved to be used in the chute system can be found, the safety alert will remain in effect. This study illustrates the importance of proper sample transport as failings can affect not only patient outcomes but also the healthcare and portering teams that are involved in the sample processing pathway.